Figure 9 from: Wallin H, Kvamme T, Bergsten J (2017) To be or not to be a subspecies: description of Saperda populnea lapponica ssp. n. (Coleoptera, Cerambycidae) developing in downy willow (Salix lapponum L.). ZooKeys 691: 103-148. https://doi.org/10.3897/zookeys.691.12880 - Wallin, Henrik; Kvamme, Torstein; Bergsten, Johannes (Zenodo, 2017)
Figure 9 - Frons. a ♀ Saperda populnea populnea (Linnaeus, 1758), Knutby (Uppland), Sweden b ♀ S. populnea lapponica ssp. n., Kiruna (Lappland), Sweden.